Cântările religioase în manualele de educație muzicală: O analiză comparativă - Mocanu, Daniel (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
The elementary notions related to the field of religious education, during schooling, are gradually acquired by going through the contents related to the three school cycles: primary, secondary and high school. In this context of the development and acquisition of religious knowledge, the contents of the school programs intended for the subject of Music Education are also included. Through the Music Education handbooks, in addition to the knowledge related to the sphere of linear music, a whole series of Christian values and attitudes, which can be derived from the religious songs, are shared with the students. Among the Christian values and attitudes transmitted through the Music Education handbooks we can list: the awareness of the contribution of church music in the spiritual and cultural life of society, the awareness of the meanings of divine worship manifested through church music and the reflective attitude on the value of church music in the life of the individual and society.